Factors affecting consumers' behavior towards online food delivery apps during the Covid-19 pandemic in Iloilo City - Sabordo, Reyban B.; Tidon, Ma. Gemma Merlge L.; Umahag, Ma. Marvi Ann L.; Villacorta, Samantha M.
The limits in movement imposed by the lockdowns made food delivery applications became very popular throughout the pandemic. The goal of the study is to learn about consumers' awareness of food delivery apps in Iloilo City during the pandemic and the many factors that influence usage and learn if these factors influence their behavior. The researchers studied behavioral intentions in reaction to the integration of new technologies such as food delivery applications using the unified theory of acceptance and use of technology (UTAUT) model. To evaluate the theoretical framework and test the proposed research hypotheses, the researchers employed an online questionnaire to collect data. The researchers performed descriptive statistical tests in identifying their level of awareness of online delivery apps. Furthermore, the researchers utilized a PLUM - Ordinal Regression which shows that performance expectancy, effort expectancy, social influence, and facilitating factors have a significant influence on consumers' behavior. amongst all of the independent variables, findings also shows taht social influence has the strongest influence towards the behavior of consumers.